Editorial - González Vargas, Paola (2021)
Art, Culture and Society: Interdisciplinary Journal of Research through Artistic Practice comes to light with this issue in the midst of the development of the CIDEA Investiga 2021 meeting with the possibility of dialoguing with different people who do research in the arts, by the arts and from the arts. The concept of artistic research is in constant construction and for this it is necessary to build a dialogue in which constructions and deconstructions about the ideas of art that are developed within the academy are put in tension. What we do and how we do it always proposes a very interesting reflection for the artist who approaches the more formal and academic spaces, whether out of interest, necessity or just curiosity. This space seeks to be a living community of knowledge that self-produces from those relationships that develop in the conversation, provoke, discuss and propose material and abstract spaces to nominate from the artistic disciplines the practices themselves, always associated with a context and its social and cultural implications. Translated with www.DeepL.com/Translator (free version)